2022
DOI: 10.1038/s41598-022-17222-y
|View full text |Cite
|
Sign up to set email alerts
|

Real-world treatment patterns for atopic dermatitis in South Korea

Abstract: The phenotypes of atopic dermatitis (AD) are diverse, and ethnic differences have been suggested. To date, few studies have explored large-scale national data on the treatment patterns of AD in Asians. Therefore, we aimed to examine real-world treatment patterns for AD, including the probability of discontinuation of AD treatment and restart after discontinuation. A retrospective observational study was conducted using the nationwide healthcare database in South Korea between January 1, 2016 to July 31, 2020. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…AD diagnosis can be made in Korea when at least 2 of the 4 major features and 4 of 14 minor features are fulfilled. These criteria have been widely used in clinical practice and studies conducted on Korean AD patients [53][54][55]. Recently, the simplified 2-plus-1 AD diagnostic criteria, which comprise two essential features and one important feature, is also recommended by the American Academy of Dermatology (AAD) [56].…”
Section: Clinical Features and Diagnostic Criteria Of Ad In Koreamentioning
confidence: 99%
“…AD diagnosis can be made in Korea when at least 2 of the 4 major features and 4 of 14 minor features are fulfilled. These criteria have been widely used in clinical practice and studies conducted on Korean AD patients [53][54][55]. Recently, the simplified 2-plus-1 AD diagnostic criteria, which comprise two essential features and one important feature, is also recommended by the American Academy of Dermatology (AAD) [56].…”
Section: Clinical Features and Diagnostic Criteria Of Ad In Koreamentioning
confidence: 99%
“…4 The prevalence of AD among adults ranged from 2.1% to 4.9% across countries, and up to 10% of adults required medication for moderate to severe AD due to inadequate response to topical therapies; the prevalence rates were higher among adult patients than among pediatric patients, of whom 1.5% required medication for moderate to severe AD. [5][6][7] As AD treatment strategies, international guidelines and expert opinions generally recommend that oral corticosteroids should generally be avoided or limited to the short term only as rescue therapy. [8][9][10][11] Nonetheless, given the benefits of oral corticosteroids, including their effectiveness in allergic diseases, short-term safety, and low cost, many patients with moderate to severe AD are treated with oral corticosteroids for prolonged periods, which may constitute inappropriate or excessive use.…”
Section: Introductionmentioning
confidence: 99%
“…Atopic dermatitis (AD) is a common chronic inflammatory skin disorder affecting approximately 11 to 20% of children and 5-8% adults. In a retrospective observational study conducted in South Korea by Lee et al,944,559 pediatric patients and 1,066,453 adults with AD were identified [1,2]. This condition, described as a heterogenous inflammatory skin disease, consists of various subtypes based on clinical (disease stage/chronicity), demographics (age, ethnicity), and molecular parameters/endotypes.…”
Section: Introductionmentioning
confidence: 99%